2001
DOI: 10.1097/00005110-200110000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Registered Nurse Retention Through Shared Decision Making

Abstract: The authors describe an organization's success in creating a process, which aligned nurses and senior management in the creation of a desired future state. The environment is one of high census, nurse shortage, and two union organizing efforts. The outcome is a significant investment in this organization's future by the selection of key interventions to enhance nurse satisfaction and loyalty, and ultimately retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…As evidenced by other studies, nurse education has a positive impact on nurse satisfaction and retention (Ndiwane 1999, Janney et al. 2001), which is also true with age and experience (Blegen 1993, Ndiwane 1999).…”
Section: Discussionmentioning
confidence: 56%
“…As evidenced by other studies, nurse education has a positive impact on nurse satisfaction and retention (Ndiwane 1999, Janney et al. 2001), which is also true with age and experience (Blegen 1993, Ndiwane 1999).…”
Section: Discussionmentioning
confidence: 56%
“…Consistently, direct positive relationships have been found between job satisfaction and nurse intention to remain employed (Chan & Morrison 2000, Kunaviktikul et al. 2000, Fletcher 2001, Janney et al. 2001, Shader et al.…”
Section: Introductionmentioning
confidence: 58%
“…Most studies also reported positive direct relationships between nurse intention to remain employed and specific components of job satisfaction, including satisfaction with pay and benefits (Chan & Morrison 2000, Kunaviktikul et al. 2000, Fletcher 2001, Janney et al. 2001, Shields & Ward 2001, Cowin 2002, Joshua‐Amadi 2002, Lacey 2003), satisfaction with scheduling (Fletcher 2001, Janney et al.…”
Section: Introductionmentioning
confidence: 99%
“…(36) Statements regarding mutual support and a sense of confidence about the changeover process were found to be associated with most empowerment factors. Many previous studies have also shown that empowerment strengthens trust in management (11,35,37). In order to become empowered, health care staff needs to have real influence and decisionmaking power over the plans concerning their work, work environment and future developing projects in organisation.…”
Section: Resultsmentioning
confidence: 99%